[For and by Filipinos ; Life in Madrid ; Barry Mania in Manila [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Tackles issues on the turnover of American military bases to the Philippines, the Cubi Point being the last of the military bases to turned over. Filipino contract workers in Spain narrating their stories to Probe Team. Barry Manilow, an American balladeer in his performance in the Philippines.